ANALYSIS OF ABILITY TO UNDERSTAND THE CONCEPT OF RELATIONS AND FUNCTIONS BASED ON APOS THEORY OF CLASS STUDENTS VIII MTsN 1 ACEH SOUTHWEST - Nuri Bahkrunnisa; Zainal Abidin; Novi Trina Sari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
The main key in learning mathematics is understanding the concept. If students are going to learn higher concepts, then students must master the concepts that underlie these concepts because mathematical concepts are arranged in a systematic, hierarchical, and real way from simple to complex things. The purpose of this study was to describe the ability to understand the concept of relations and functions based on APOS theory. The research method used is descriptive qualitative with six research subjects, consisting of grade VIII-A2 UBP students at MTsN 1 Aceh Barat Daya. Subject selection is based on certain student ability criteria, namely 2 students with high abilities, 2 students with moderate abilities, and 2 students with low abilities. The data collection technique used was a concept understanding test sheet and interview guidelines. Data analysis is done by reducing, presenting, and drawing conclusions. The results showed that: Subjects with high ability (ST) fulfilled all indicators of concept understanding. Subjects with moderate ability (SS) and subjects with low ability (SR) only have 4 indicators of concept understanding. In indicator (1) the ST subject meets the action stage, while the SS subject and SR subject do not meet the APOS stage. In indicator (2), the ST subject fulfills the process, object and schema stages, the SS subject fulfills the process and object stages, the SR subject only meets the object stage. In indicator (3), the ST subject fulfills the action, process and object stages, the SS subject fulfills the action and process stage, the SS subject fulfills the process and object stage. In indicator (4) the ST subject fulfills the process, object and schema stages, the SS subject and SR subject only fulfills the process stage. In indicator (5) the ST subject meets the process and object stages, the SS and SR subjects only meet the process stage.